2020
DOI: 10.1155/2020/8814574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Mesenchymal Stem Cells with Their Extracellular Vesicles on the Treatment of Kidney Damage Induced by Chronic Renal Artery Stenosis

Abstract: Background. Chronic renal artery stenosis is considered one of the most common causes of renovascular hypertension (RH). Chronic hypoxia can lead to irreversible damage to renal tissue and to a progressive deterioration of renal function. We have previously shown that bone marrow-derived mesenchymal stem cells (BMSCs) improved renal parenchyma and function in a model of RH (2 kidneys, 1 clip model (2K-1C) in rats. Microvesicles (MVs) and exosomes (EXs) released by MSCs have been shown to induce effects similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The addition of MSC-EVs during HMP attenuated the ischemic kidney injury through maintaining the enzymatic machinery critical for cell survival and reduced the reperfusion damage to kidney ( 117 ). Beneficial properties of AD-MSC-Exos were also reported in the 2K-1C ( 118 ), a renal artery stenosis model. Administration of AD-MSC-Exos were demonstrated to stabilize the systolic blood pressure (SBP), downregulate hypoxia marker HIF-1a and reduce profibrotic gene collogen and TGF-β expression, thus mitigating kidney fibrosis ( 118 ).…”
Section: Therapeutic Potential Of Msc-exos For Ckdmentioning
confidence: 60%
See 1 more Smart Citation
“…The addition of MSC-EVs during HMP attenuated the ischemic kidney injury through maintaining the enzymatic machinery critical for cell survival and reduced the reperfusion damage to kidney ( 117 ). Beneficial properties of AD-MSC-Exos were also reported in the 2K-1C ( 118 ), a renal artery stenosis model. Administration of AD-MSC-Exos were demonstrated to stabilize the systolic blood pressure (SBP), downregulate hypoxia marker HIF-1a and reduce profibrotic gene collogen and TGF-β expression, thus mitigating kidney fibrosis ( 118 ).…”
Section: Therapeutic Potential Of Msc-exos For Ckdmentioning
confidence: 60%
“…Beneficial properties of AD-MSC-Exos were also reported in the 2K-1C ( 118 ), a renal artery stenosis model. Administration of AD-MSC-Exos were demonstrated to stabilize the systolic blood pressure (SBP), downregulate hypoxia marker HIF-1a and reduce profibrotic gene collogen and TGF-β expression, thus mitigating kidney fibrosis ( 118 ). Interestingly, the treatments with AD-MSC-Exos, AD-MSC or AD-MSC-EVs were equally effective in reducing the expression of the fibrotic markers collagen-1 (COL-1) and TGF-β.…”
Section: Therapeutic Potential Of Msc-exos For Ckdmentioning
confidence: 60%
“…Additionally, there are functional differences in efficacy between EV subtypes. A recent study found adipose-MSC-MVs reduced proteinuria while only exosomes promoted natriuresis following chronic renal artery stenosis [ 147 ]. To minimise these effects, studies were compared based on the ISEV recommendations, according to the source of MSCs, EV subtype, protein content of administered EVs, and route of injection [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In β-integrin signalling, TGF-β forms a complex with Smad and binds transcription factors, such as Snail, to downregulate expression of epithelial cell markers (E-cadherin), and activate expression of fibrosis-associated stromal cell markers (α-SMA, fibronectin, collagen I) [ 143 ]. Erythropoietin (EPO)-transfected microparticles in mice with UUO [ 144 , 145 ], Wharton jelly’s MSC-EVs in cyclosporin A injury [ 146 ], and adipose-MSC-EVs in renal artery stenosis [ 147 ] all inhibited the EMT and tubulointerstitial fibrosis by downregulating phosphorylated Smad2, Smad3, and p38 MAPK signalling, and increasing E-cadherin.…”
Section: Anti-fibrotic Effect Of Msc-evs In Ckdmentioning
confidence: 99%
“…Stem cell-derived exosomes possess favorable pharmacokinetic property, biocompatibility, and tissue-targeting ability owing to their bilayer structures and constituents of mRNAs, microRNAs, cytokines, chemokines, and immunomodulatory compounds (Mendt et al, 2019;Harrell et al, 2019;Haraszti et al, 2019;Fernández-Francos et al, 2021). Moreover, the ability of the exosomes to suppress inflammation, regulate cell proliferation, and promote damaged tissue repair has been corroborated (Harrell et al, 2019;Massa et al, 2020), for example, in the skin , muscle and bone (Nakamura et al, 2015;Hao et al, 2017;Mianehsaz et al, 2019), nerve (Tsintou et al, 2021), heart (Bahardoust and Baghoi-Hosseinabadi, 2021), liver , kidney (Ishiy et al, 2020), lung (Xu et al, 2020), immune system (Burrello et al, 2016), cancer (Sharma, 2018), and virus infection (Jamshidi et al, 2021) (Figure 2). Introduction of the exosomes into biomaterials, such as exosome-laden hydrogel (Wang et al, 2019a;Wang et al, 2019b), exosome-coated scaffold (Zhai et al, 2020;Kyung Kim et al, 2021), and exosome-based drug delivering vectors (Barile and Vassalli, 2017;Mehryab et al, 2020), has Figure 1 Biogenesis and identification of exosomes.…”
Section: Introductionmentioning
confidence: 99%